Analisis Dimensi Utama dalam Wacana Teodisi - Nurhanisah Senin; Hamidun Mohamad Husin; Norsaleha Mohd Salleh Mohd Salleh; Nazneen Ismail; Mustafa Kamal Amat Misra (Penerbit Universiti Islam Selangor, 2026)
Indexed by MyCite